The school representation of the social sciences in second chance programs - García Monteagudo, Diego (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The aim of this study is to know the perception that students from school peripheries have about the social sciences. For this, an instrument has been designed and validated, with the aim that 120 students from public secondary schools in the Valencian Community can provide information on their learning of social sciences, the teaching strategies carried out by teachers and their assessment, of the citizen formation of those didactic projects that work the socially relevant problems. The perception of the social sciences is optimal and with more significant differences between the two analyzed courses.